Administering SQL server 7 - Chaturvedi, Divya (McGraw-Hill, 1999)
The book provides an easy and systematic way for learning application development and system management. It also helps readers in writing efficient SQL, understanding database replication concepts, and finetuning and monitoring the server. It offers information about optimizing SQL queries and server configuration in order to enhance overall application performnce. It not only describes the functionality but also explains the concept behind it.